Drug management for migraine with aura and treatment alternatives: a case report - Deléo, Rhayra Alani Villa; Pinto, Antônio Carlos Guimarães; Amaral, Priscila Cristian do; Souza, Pietra Monique de; Barroso, Andressa Eliziário (Headache Medicine, 2022)
Introduction Migraine is a chronic disease and affects about 15% of the World population. It is the second most disabling disease among young adults. Pathophysiology has not yet been fully clarified, but there is evidence for genetic alterations that cause a state of hyperexcitability and metabolic alterations that make the central nervous system more susceptible to external stimuli. Objective To present the evolution of a diagnosis of headache with aura treated with drugs and the results obtained. Methods Data collected through complete anamnesis. Results/Case report Woman, 26 years old, student, white, with hypothyroidism, denies smoking and alcohol consumption. Reports practicing physical activity and maintaining a healthy diet. Complains of headache for 9 years, with increased intensity and frequency. At the age of 18, period of onset of pain, frequency was every 10-15 days, with a maximum duration of one day and visual changes. She was using oral contraceptive pill (OCP) and dipyrone, without neurological consultation. At the age of 20, the use of OCP ceased, with worsening of the frequency and intensity of pain, the patient sought specialized medical care. Neurologist diagnosed migraine with aura triggered by stress. As treatment, he prescribed 50 mg/day of topiramate divided into two doses and alprazolam 0.5 mg, with return in 60 days. Reports no improvement and there was an increase in topiramate dosage to 100 mg and alprazolam dosage to 1 mg/day. There was relative improvement for an approximate period of 4 months. Patient returned to daily pain, with episodes of throbbing pain, with exacerbated photo and phonophobia, need for hospital care twice a month and beginning of concentration problems. In hospital care, reports having received tramal, profenid and dramin. (To see the complet abstract, please, check out the PDF.)